Analisis Penyelenggaraan Pemilihan Kepala Daerah Dimasa Pandemi Covid-19 Berdasarkan Undang-Undang Nomor 6 Tahun 2020 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2020 Tentang Perubahan Ketiga Atas Undang-Undang Nomor 1 Tahun 2015 Tentang Pemilihan Gubernur, Bupati, dan Walikota (Studi di KPU Kota Bandar Lampung) - Lintje Anna Marpaung; Baharudin Baharudin; Anggalana Anggalana; Muhammad Affandi (Universitas Batanghari Jambi, 2021)
The Regional Head election event which is expected to be held in September has to be postponed until December of course the postponement of the schedule is not without reason, the widespread spread of the Covid-19 pandemic virus outbreak is a separate obstacle for the General Election Commission to be able to hold Regional Head Elections because Public safety is the main thing that must be considered by the General Election Commission because this virus can attack anyone and the worst impact is the death of a person, therefore the General Election Commission made a new method related to regional head elections, namely by implementing health protocols in place. voting which will be applied to all officers to people who already have voting rights under the law this mechanism will be applied to voters from normal body temperature, body temperature 37.3 degrees Celsius to voters exposed to Covid-19 In addition to a more complicated mechanism, the impact resulting from Covid-19 is a more complicated election than before and the cost of organizing it is more expensive because it has to use a health protocol tool that must be given to all officers and the public.